Mitigation of money laundering risk in Malaysia: a Maqasid al-Shari‘Ah perspective / Muhammad Nazmul Hoque ... [et al.] - Hoque, Muhammad Nazmul; Abdullah, Md. Faruk; Mat Isa, Yusarina; Hasnan, Suhaily; Mohamed, Norhayati (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
This study aimed to explore the role of maqasid al-Shari‘ah towards mitigating money laundering risk in Malaysia. This study adopted a qualitative approach to fulfil its objective. The data were collected through document analysis and semi-structured interviews with the experts. This study revealed that money laundering goes against the principles of Shariah as it leads to consuming other’s property illegally and disregarding justice and welfare among the people. Maqasid al-Shari‘ah plays a vital role in preventing money laundering through several ways, which includes the condition of (1) circulation (rawaj) of wealth among people, (2) transparency (wuduh) in transaction, and (3) justice (‘adl) among transacting parties. To mitigate money laundering, maqasid al-Shariah suggests the reporting of suspicious transactions and proper documentation to be practised among bankers. The outcome of this study may help motivate bankers and their clients to be more aware of the role of maqasid al-Shari‘ah in combating money laundering. Moreover, it may help policymakers and financial institutions look for alternative ways to mitigate money laundering risks.